Gen-Z and Urban Waste Management Policy: Uncovering Perceptions and Forms of Action - Putu Bella Cytnhia Dian Utami; Gede Sri Darma (Dinasti Publisher, 2025)
Urban waste management is a major challenge in sustainable development, especially in cities with high consumption levels such as Denpasar. Generation Z as a demographic group that grows in the digital era has great potential in supporting waste management policies. This study aims to analyze the perception and participation of Gen-Z in waste management policies in the city of Denpasar and identify the factors that affect their involvement. A qualitative method with a phenomenological approach was used in this study, where primary data was obtained through structured interviews with 24 Gen-Z respondents who were purposively selected through questionnaires on the https://bit.ly/PersepsiPartisipasiGenZ link, as well as semi-structured interviews with representatives of relevant government elements. Secondary data includes policy documents and reports related to waste management in Denpasar City. Data analysis was carried out using the analysis of the model of Miles and Huberman (1994) which included three main stages, namely data reduction, data presentation, and drawing conclusions to identify the main themes related to perception and participation. The results show that attitudes towards policies, subjective norms, and perceptions of behavioral control play a significant role in encouraging or inhibiting Gen-Z's participation in waste management. The majority of Gen-Z has a positive perception of the applicable waste management policies. This perception brings Gen-Z participation to the level of acting together based on the theory of participation levels by Wilcox (1994), where environmental awareness, community support and information accessibility are supporting factors, while the lack of adequate waste management facilities, weak regulatory enforcement, a suboptimal waste transportation system, and bureaucratic flows that seem slow and convoluted are still factors inhibiting Gen-Z participation.